Early detection and health education of hypertension in adolescents - Abdullah Azam Mustajab; Siti Khoiriyah (Universitas Muhammadiyah Magelang, 2023)
Hypertension is a dangerous disease as a risk factor for cardiovascular disease which is the main cause of death. Generally, hypertension occurs in adults or the elderly, but it can also occur in adolescents. Adolescents who experience hypertension have a higher risk of developing coronary heart disease or kidney failure as adults. The purpose of community service is to carry out early detection of hypertension in adolescents and increase youth knowledge about hypertension as a primary prevention effort. The method used is health checks and health education. Activities carried out by checking blood pressure, filling out questionnaires and conducting health education about hypertension. The results of blood pressure checks showed that 225 adolescents (98.68%) were in normal condition and 3 adolescents (1.32%) had mild hypertension. While the results of the questionnaire on adolescent knowledge of hypertension found that 198 adolescents (86.84%) had good knowledge and 30 adolescents (13.16%) had sufficient knowledge.